2008
DOI: 10.1073/pnas.0800884105
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope evidence for an amphibious phase in early proboscidean evolution

Abstract: The order Proboscidea includes extant elephants and their extinct relatives and is closely related to the aquatic sirenians (manatees and dugongs) and terrestrial hyracoids (hyraxes). Some analyses of embryological, morphological, and paleontological data suggest that proboscideans and sirenians shared an aquatic or semiaquatic common ancestor, but independent tests of this hypothesis have proven elusive. Here we test the hypothesis of an aquatic ancestry for advanced proboscideans by measuring ␦ 18 O in tooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 53 publications
5
36
0
Order By: Relevance
“…The recent isotope analysis of Barytherium's enamel sug− gested that it grazed freshwater vegetation in a swamp or riverine environment (Liu et al 2008), supporting this sugges− tion. Similar results were obtained from the enamel of Moeri− therium.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The recent isotope analysis of Barytherium's enamel sug− gested that it grazed freshwater vegetation in a swamp or riverine environment (Liu et al 2008), supporting this sugges− tion. Similar results were obtained from the enamel of Moeri− therium.…”
Section: Resultsmentioning
confidence: 86%
“…The recovery of a few weathered remains of an old individual at the begin− ning of the twentieth century in the Qasr El Sagha Formation of the Fayûm led to the description of its type species, B. grave Andrews, 1901. Very few discoveries (consisting of isolated remains only) referable to the genus have been re− ported in the region since (Harris 1978;Holroyd et al 1996), though many new specimens have been recovered from the Birket Qarun Formation in recent years (Seiffert 2007;Liu et al 2008; Seiffert et al 2008). In contrast, hundreds of cra− nial, dental and postcranial elements referable to Barythe− rium, including a partial skeleton, were discovered at Dor El Talha (Savage 1969).…”
Section: Introductionmentioning
confidence: 95%
“…In Proboscidea, isotopic analysis suggest that stem taxa ( Moeritherium and Barytherium ) may have feed on freshwater plants and lived in freshwater swamps [40]. This assertion is supported by the study of developmental growth in modern elephants which has shown that they display some characters involving a past adaptation to life in water (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…(33,35,50) However, many other sequence-based studies do not support this clade, some favoring Sirenia-Hyracoidea (7,32,38,40) and others favoring Proboscidea-Hyracoidea. (37) Recent support (56,57) for the relatively old idea that some early proboscideans were semiaquatic (54) underscores the morphological basis for the proboscidean-sirenian clade. Instability within Afroinsectiphilia (insectivoran-grade afrotherians plus the aardvark) concerns primarily the position of Tubulidentata.…”
Section: Afrotheriamentioning
confidence: 99%